Laju Pertumbuhan Tanaman dan Produksi Dua varietas Kacang Hijau (Phaseolus radiatus L.) Dengan Pemeberian Pupuk Guano - Desy Lavria; lisa Mawarni; Asil Barus (Jurnal Agroekoteknologi, 2015)
The aim of this research was aplication guano on mung bean which hope to can increase the growth and production. This research was conducted at experimental field of Agriculture Faculty USU in Juli-September 2014 using factorial randomized block design with two factor, i.e. types of varieties (betet and walet) and guano (none; 200; 400 and 600 kg/ha). Parameter observed were relative growth rate and dry weight of seeds per sample. The result showed that varieties and guano application significantly affect the parameters of relative growth rate in the 10-21 day after planted (DAP). The interaction of two factor significantly affect on parameters dry weight of seeds per sample. However application of guano on mung bean no significant effect the parameters crop growth rate, days to flowering, days to harvesting, number of seed per sample, weight of 1000 seed and seed production per plot.Keywords : mung bean, varieties, guano